An Analysis of Short Story The Little Match Girl by Hans Christian Andersen in Semantics Perspective - Ni Wayan Swarniti (PRAGMATICA : Journal of Linguistics and Literature, 2024)
This research aims to analyze the antonymy and synonym existed in a short story titled “The Little Match Girl” by Hans Christian Andersen. This research employs a qualitative semantics analysis to investigate the underlying meanings and implications of the language used in "The Little Match Girl," a short story written by Hans Christian Andersen. Using antonymy and synonymy as the main focus, the research demonstrates how these semantic elements can be used to convey meaning and shape the underlying themes, motifs, and messages of the story. The instrument of this research was the researcher herself. Document analysis as the data collection technique, and document analysis as the data analysis technique. The data for this research was collected through reading deeply and analysis of "The Little Match Girl," which was chosen as the source of this research. The results of this research demonstrated the value of semantics as a grand theory in literary analysis, and highlights the importance of antonymy and synonymy as powerful tools for conveying meaning in literature. The analysis of this short story provided a deeper understanding of the meanings and implications of the language used, and how it contributes to the story's themes, motifs, and messages. These findings could be used as a model for further analysis of literature texts and can provide insight for future research on semantics.